Respective Contributions of URT1 and HESO1 to the Uridylation of 5′ Fragments Produced From RISC-Cleaved mRNAs - Zuber, Hélène; Scheer, Hélène; Joly, Anne-Caroline; Gagliardi, Dominique (Frontiers in Plant Science, 2018)
In plants, post-transcriptional gene silencing (PTGS) represses gene expression by translation inhibition and cleavage of target mRNAs. The slicing activity is provided by ARGONAUTE 1 (AGO1), and the cleavage site is determined by sequence complementarity between the target mRNA and the microRNA (miRNA) or short interfering RNA (siRNA) loaded onto AGO1, to form the core of the RNA induced silencing complex (RISC). Following cleavage, the resulting 5’ fragment is modified at its 3’ end by the untemplated addition of uridines. Uridylation is proposed to facilitate RISC recycling and the degradation of the RISC 5’-cleavage fragment. Here, we detail a 3’ RACE-seq method to analyze the 3’ ends of 5’ fragments produced from RISC-cleaved transcripts. The protocol is based on the ligation of a primer at the 3’ end of RNA, followed by cDNA synthesis and the subsequent targeted amplification by PCR to generate amplicon libraries suitable for Illumina sequencing. A detailed data processing pipeline is provided to analyze nibbling and tailing at high resolution. Using this method, we compared the tailing and nibbling patterns of RISC-cleaved MYB33 and SPL13 transcripts between wild-type plants and mutant plants depleted for the terminal uridylyltransferases (TUTases) HESO1 and URT1. Our data reveal the respective contributions of HESO and URT1 in the uridylation of RISC-cleaved MYB33 and SPL13 transcripts, with HESO1 being the major TUTase involved in uridylating these fragments. Because of its depth, the 3’ RACE-seq method shows at high resolution that these RISC-generated 5’ RNA fragments are nibbled by a few nucleotides close to the cleavage site in the absence of uridylation. 3’ RACE-seq is a suitable approach for a reliable comparison of uridylation and nibbling patterns between mutants, a prerequisite to the identification of all factors involved in the clearance of RISC-generated 5’ mRNA fragments.